Motivation to Memorize the Quran in Building Discipline Character of Santri Pesantren Muhammadiyah Ahmad Dahlan Tegal Regency - Pujiarto, Redi; Hasan, Ibnu; Darodjat, Darodjat (Eduvest - Journal of Universal Studies, 2025)
Muhammadiyah Ahmad Dahlan Islamic Boarding School in Tegal Regency has a strate-gic role in shaping the character of the young generation through superior programs based on the Quran. This study aims to analyze the contribution of motivation to mem-orize the Quran to the formation of the disciplined character of students in this Islamic boarding school. The study used a qualitative approach with data obtained through interviews, observations, and document analysis. The results of the study indicate that programs such as Dauroh Tahfidz and the memorization cadre program play an im-portant role in training students to maintain consistency, responsibility, and time man-agement. The motivation of students is driven by sincere intentions because of Allah SWT, parental encouragement, and intensive guidance from tahfidz teachers through a creative and supportive approach. In addition to memorizing the Quran, students are also trained through extracurricular activities to reduce boredom and support educa-tional balance. This program not only produces competent hafidz, but also forms a strong Islamic character. This study provides a new contribution to the study of religion-based character education, especially in the Muhammadiyah Islamic boarding school environment. Thus, the motivation to memorize the Quran is proven to be an important instrument in the formation of the disciplined character of students who are oriented towards spiritual values and morality.